(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper explores the framing of Palestine as a symbol of anti-colonial struggle within Indonesian nationalist discourse and solidarity movements. Drawing on Indonesia’s own history of resistance against Dutch colonial rule, the paper argues that many in Indonesia perceive the Palestinian struggle for independence as an extension of their own anti-colonial history. The study investigates how this shared history of resistance has fostered strong public and political support for Palestine, particularly among nationalist groups and political activists. By analyzing historical texts, speeches, and cultural references, the paper explores how Palestinian liberation is framed as an integral part of the global struggle against colonialism and imperialism. The study also examines the evolution of Indonesian solidarity movements with Palestine, from early post-independence support to contemporary youth-led activism, and the way this solidarity has influenced national identity and political discourse in Indonesia.